Temporal retinal sensitivity in mesopic adaptation - Matesanz, Beatriz M (2011)
Purpose: Night driving is a complex visual task with important ramifications for driver and pedestrian safety. It is usually performed under mesopic or scotopic conditions and frequently, in the presence of transient glare sources that can adapt parts of the central retina. The objective of this work was to analyze the time response of adaptation for the central 15° of the retina when part of it is exposed to transient or steady mesopic adapting fields. Methods: Absolute visual thresholds and luminance thresholds when viewing steady and transient adaptation fields were measured for three observers, at temporal retinal eccentricities of 0°-14.5° in steps of 2.9° (subsequently described as 0°, 3°, 6°, 9°, 12° and 15°) using a two-channel Maxwellian view optical system. The adaptation field and stimulus subtended 1.05° and 0.45° respectively. The transient adaptation field was presented with a stimulus onset asymmetry (SOA) of 300ms. Time course adaptation curves were also measured at 0°, 6° and 9° Results: The absolute dark adaptation threshold (threshold measured at dark adaptation conditions or ) decreases in peripheral retina due to an increasing rod contribution. Luminance thresholds vs eccentricity curves for transient () and steady () mesopic adaptation fields intersect across the first 15° of the peripheral retina. Conclusions: While the fovea shows higher sensitivity than the areas of peripheral retina investigated in this study, the speed of adaptation, measured from the visibility loss, is greater for retinal regions between 6° and 9° than for the fovea or retinal eccentricities beyond 9°.